Social and Historical Reasons of an Individuals’ Moral Crisis (Eurasian Scientific Herald, 2023)
Morality always becomes the central topic of all disciplines including sociology, psychology, psychoanalysis and literature. Throughout human history, rapid changes in society cause moral crisis of human beings. In addition to this, moral identity is known as the base of morality and is tied to judgments of personal responsibility and integrity or the realization. Each individual differs in moral identity, moral motivation and personality development. This article focuses on identifying social and historical reasons of appearance individuals’ moral crisis.